Cloud Computing: Methodology, Systems, and Applications - Wang, Lizhe (CRC Press, 2017)
Designed for researchers, engineers, IT professionals, and graduate students in parallel and cloud computing, this volume covers the state of the art in cloud computing theory and practice. It spans the background, concepts, services, and middleware of cloud computing. A range of scientific researchers and professors in cloud computing, grid computing, high-performance computing, and Internet computing discuss enabling techniques, system implementation, service functionalities, and various applications. Numerous case studies are included throughout the text.